2009
DOI: 10.1136/jech.2009.088740
|View full text |Cite
|
Sign up to set email alerts
|

Real world reviews: a beginner's guide to undertaking systematic reviews of public health policy interventions

Abstract: Background The systematic review is becoming an increasingly popular and established research method in public health. Obtaining systematic review skills are therefore becoming a common requirement for most public health researchers and practitioners. However, most researchers still remain apprehensive about conducting their first systematic review. This is often because an 'ideal' type of systematic review is promoted in the methods literature. Methods This brief guide is intended to help dispel these concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…The methods are intended to be transparent and therefore replicable, and to minimise selection bias. Systematic review is increasingly used to inform the development of policy and identify gaps in the research literature (Bambra, 2011;Dobbins, Jack, Thomas et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The methods are intended to be transparent and therefore replicable, and to minimise selection bias. Systematic review is increasingly used to inform the development of policy and identify gaps in the research literature (Bambra, 2011;Dobbins, Jack, Thomas et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review uses an explicit, rigorous, and transparent methodology for identifying, selecting, and coding papers (Greenhalgh et al, 2005). It aims to support evidence based policy and practice (Chalmers, 2003) through the identification of the best available evidence for a particular research question (Bambra, 2011). To ensure rigor and transparency, a systematic review should follow an established process for: (1) identifying the review question; (2) locating and selecting relevant studies; (3) critically appraising the selected studies; (4) analyzing and synthesizing the findings from the studies; and (5) reporting (and disseminating) the review findings (Briner and Rousseau, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It is a population level intervention and should be judged as such. [6][7][8][9][10][11][12][13][14][15] Therefore, measurement of the impact of water fluoridation is not like a clinical intervention for the following reasons. First, the context in which water is fluoridated is complex: 16,17 its introduction and maintenance requires legislation, installation and maintenance of equipment, technical training of water treatment plant operators, development and adherence to procedures and processes, and continuity of supply and regular monitoring.…”
Section: The Nature Of Water Fluori-dation Programmesmentioning
confidence: 99%
“…Although RCTs are the method of choice for evaluating the effectiveness of medicines and some clinical interventions, literature published during the past 20 years has indicated that they are inappropriate for evaluating public health preventive programmes and other complex interventions. [6][7][8][9][10][11][12][13][14][15] Using water fluoridation as an example, it is not possible to randomly assign individuals to fluoridated and non-fluoridated water supplies. RCTs may have high internal validity, but they also may have poor external validity.…”
Section: Design Of Studymentioning
confidence: 99%